A complex network based simulation approach to predict the electrical properties of nanocomposites - Simões, Ricardo (2010)
It is well known that the addition of conducting fillers to a polymeric matrix can result in a significant improvement of its electrical and mechanical properties. Although the electrical properties of heterogeneous composites have been widely investigated in the past years, the electrical properties of composites containing carbon nanotubes are not sufficiently understood. In order to explore the potential application of complex network methods to nanocomposites, we developed a computer model that employs the Graph theory to represent and study such physical systems. From the virtual models of nanotube networks dispersed in dielectric polymeric matrices and by applying the boundary element method to numerically solve an electro-quasistatic problem, we build a weighted network. The developed model can easily be adapted to the study of a variety of issues related to electrical behavior of filled nanocomposites. In this paper we present results from simulations aimed at studying the effect of orientation of individual nanotube and distance between pairs of nanotubes on the capacitance. The study was also extended to the effect of the alignment of the entire nanotube network on the dielectric constant and the dielectric strength of the nanocomposite.